Generating water/MeOH-soluble and luminescent polymers by grafting 2, 6-bis(1, 2, 3-triazol-4-yl)pyridine (btp) ligands onto a poly(ethylene-alt-maleic anhydride) polymer and cross-linking with terbium(iii). Issue 7 (30th January 2023) - Hegarty, Isabel N.; Henwood, Adam F.; Bradberry, Samuel J.; Gunnlaugsson, Thorfinnur
Abstract : The synthesis of two new green emitting polymers, made by reacting the btp ligand 1 with the commercially available P(E- alt -MA) polymer and cross-linking with Tb(iii ), is described. Abstract : The synthesis of two new polymers made from P(E- alt -MA) (poly(ethylene- alt -maleic anhydride) and possessing 2, 6-bis(1, 2, 3-triazol-4-yl)pyridine (btp ) ligand side chains in 3 and 6 mol%, respectively (P1 and P2, respectively) is described. These polymers were shown to be soluble in MeOH solution and, in the case of P1, also in water, while P2 needed prolonged heating to enable water dissolution. Btp ligands are known for coordinating both d- and f-metal ions and so, herein, we demonstrate by using both UV-Vis absorption, fluorescence emission, as well as time-gated phosphorescence spectroscopies, that both P1 and P2 can bind to Tb(iii ) ions to give rise to luminescent polymers. From the analysis of the titration data, which demonstrated large changes in the emission intensity properties of the polymer upon Tb(iii ) binding (ground state changes were also clearly observed, with the absorption being red-shifted at lower energy), we show that the dominant stoichiometry in solution is 1 : 2 (M : L; Tb(iii ) : btp ratio) which implies that two btp ligands from the polymer background are able to crosslink through lanthanide coordination and that the backbone of the polymer is very likely to aid in coordinating the ions.